Pengembangan Media Pembelajaran Pop-up Book pada Mata Pelajaran IPAS BAB 7 Bagaimana Mendapatkan Semua Keperluan Kita Peserta Didik Kelas IV Di SDN Kepatihan 02 Jember - Zidnie Nidya Aldhana (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research aimed to describe the development stages of a 3D Pop-up Book learning media for Fourth-Grade IPAS and to evaluate its validity, practicality, and effectiveness under the Merdeka Curriculum framework. Using the Borg and Gall Research and Development (R&D) model restricted to the eighth stage (product effectiveness testing), data were gathered through observations, interviews, expert validation sheets, student questionnaires, and pre-test/post-test assessments. The validation results from three independent experts (language, material, and media specialists) achieved an average product validity score (Valpro) of 88.66, classifying the book as highly valid and feasible for instructional implementation. In terms of practicality, the media was rated as highly practical, securing a 94.09% score during limited testing at MI Ar-Roudhoh and an 87.80% score during large-scale field implementation with 28 fourth-grade students at SDN Kepatihan 02 Jember. Furthermore, effectiveness evaluation demonstrated a significant impact on student outcomes; the class average rose from 67.68 in the pre-test to 87.32 in the post-test, reflecting a 29.02% achievement gain. This improvement was supported by a normalized gain (N-Gain) score of 0.64, falling into the moderate growth category, with a 100% classical mastery rate. In conclusion, the developed Pop-up Book successfully met the criteria of being exceptionally valid, highly practical, and significantly effective, making it a highly recommended contextual resource to concrete abstract socio-economic concepts for elementary school students.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: IPAS Learning; Learning Media; & Pop-up Book.